Binaphthalene Boronic Acid Sensor for Saccharides and d‐Fructose Determination in Beverages. Issue 3 (5th April 2022) - Penavic, Andrej; Radujevic, Aco; Pushina, Mariia; Anzenbacher, Pavel
Abstract: The presence of electron rich compounds such as amines added to the fluorescent methoxybinaphthalene boronic acid results in a dramatic increase in affinity of diols to the aryl boronic acid as well as in the augmented fluorescence response. This is likely the result of the change in boron geometry upon coordination with electron donor which facilitate the diols binding. Here, we demonstrate the role of amino alcohol additive in binding of saccharides by boronic acid‐based fluorescent sensor. We show that this strategy allows a poorly responsive sensor to become a highly sensitive probe for the detection of sugars, which could be used for classification of saccharides as well as for quantitative analysis in DMSO‐water solutions. The simple binaphthalene boronic acid sensor was particularly sensitive to d ‐fructose ( Ka =2.08×10 6 ), which allowed for identification of commercial sweetened beverages based on their d ‐fructose content. The same method was successfully used for the quantitative analysis of d ‐fructose in soft beverages. Abstract : The sensitivity enhancement of a simple binaphthalene boronic acid sensor towards saccharides achieved by addition of 2‐methyl‐2‐aminopropanol as additive is reported in this work. The applicability of the sensor was demonstrated by quantitative analysis of d ‐fructose in commercial soft beverages.